Control of poliomyelitis by pulse immunisation in Vellore, India. Issue 6358 (1st January 1983) - John, T J; Pandian, R; Gadomski, A; Steinhoff, M; John, M; Ray, M
Abstract : In a simple study into the control of polio in the Third World a town was divided into 16 zones and pulses or oral polio vaccine given at one station in each zone, after extensive publicity about the campaign. Some 62% of children received three doses of the vaccine and the incidence of polio fell dramatically over the study period. It is suggested that this method is applicable to similar communities because it is cheap, effective, and able to be extended to unimmunised communities when resources allow.